Eco-Sustainable Development in Puncak Bintang Jawa Barat Indonesia - Octavianti, Meria; Agustin, Herlina (International Journal of Psychosocial Rehabilitation, 2020)
Eco-sustainable development is a conscious and planned effort that integrates the environment, including the resources, into the development process to ensure the welfare and the quality of present and past life generations. Converting a production forest into excursion is a form of eco-sustainable development. This study seeks to provide an overview of the role of communication in eco-sustainable development in North Bandung, specifically Puncak Bintang, in the success of the forest conversion. This research used qualitative method with case study approach. Considering the approach, the researchers collected data from many sources related to the topic under study. They observed a number of activities of Perum Perhutani and the community at several excursion forests and interviewed the head of Perum Perhutani KPH Bandung Utara, forest villagers and visitors to collect primary data. Secondary data were obtained from literature review on relevant documents. The results showed that Community-Based Forest Management (CBFM) proclaimed by the State-Owned Forestry Enterprise (Perhutani) is an implementation of eco-sustainable development. The communication between the company and the forest villagers, that was once top-down, linear and unidirectional, thanks to CBFM, is now transformed into horizontal, interactive, and dialogical. This led to a solid foundation for the success of forest conversion in Puncak Bintang that it eventually improved the welfare of the villagers as well as preserved the forest for the next generations.